Elevation [videorecording (DVD)] - Glenn, John (Producer); Roman, Jacob; Ryan, Kenny; Salinas, H. Scott; Mackie, Anthony, 1978-; Baccarin, Morena; Hasson, Maddie, 1995- (Vertical, 2025)
Set in the post-apocalyptic Rocky Mountains, a single father and two women venture from the safety of their homes to face monstrous creatures to save the life of a young boy.